2012
DOI: 10.3748/wjg.v18.i30.3923
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin as potential biomarker and therapeutic target in gastric and liver cancers

Abstract: Gastric cancer and liver cancer are among the most common malignancies and the leading causes of death worldwide, due to late detection and high recurrence rates. Today, these cancers have a heavy socioeconomic burden, for which a full understanding of their pathophysiological features is warranted to search for promising biomarkers and therapeutic targets. Osteopontin (OPN) is overexpressed in most patients with gastric and liver cancers. Over the past decade, emerging evidence has revealed a correlation of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 84 publications
3
87
1
1
Order By: Relevance
“…Available literature data suggested that osteopontin expression acts as a biomarker of clinical aggressiveness in patients with more advanced disease stage [9]. In our study, The p value is from the two-sided Wald test CI 95 % confidence interval of hazard ratio, COX-2 cyclooxygenase 2, HR hazard ratio, TNM tumor-node-metastasis…”
Section: Subgroup Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Available literature data suggested that osteopontin expression acts as a biomarker of clinical aggressiveness in patients with more advanced disease stage [9]. In our study, The p value is from the two-sided Wald test CI 95 % confidence interval of hazard ratio, COX-2 cyclooxygenase 2, HR hazard ratio, TNM tumor-node-metastasis…”
Section: Subgroup Analysesmentioning
confidence: 99%
“…Functional E-cadherinb-catenin adhesion complexes are involved in anchorage mechanisms, and b-catenin is also involved in the Wingless/Wnt signaling pathway and transcription activation. Osteopontin, an integrin-binding glycophosphoprotein cytokine, plays an important role in cancer cell adhesion, protection from apoptosis, invasion, and migration [9] via the degradation of extracellular matrix, angiogenesis, and cell survival [10]. Literature data have documented that osteopontin expression is related to metastatic potential, and may be a prognostic marker in several tumor types, including GC, and especially in patients with more advanced disease stage [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human malignant melanoma, OPN expression is significantly associated with reduced relapse-free survival and additional histological parameters that are associated with poor clinical outcome [7,24,29,33]. OPN is a prognostic marker in a variety of cancers [30,[39][40][41]. In metastatic and primary melanomas, OPN has also been suggested to be a novel promising biomarker for the detection of metastases in patients with primary melanomas [24,[42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…OPN, secreted by osteoblasts, osteoclasts, and osteocytes, is important in mineralization and bone resorption [9]. Recently, this protein was found to be relevant in regulation of immunity and inlammation, angiogenesis, oncogenesis, cancer progression, and apoptosis [10][11][12]. OPN interacts with most cells using two binding domains.…”
Section: Introductionmentioning
confidence: 99%